Authority, Intellectual Networks and Politics in the Canonization of Ṣaḥīḥ Al-Bukhārī and Ṣaḥīḥ Ibn Ḥibbān - Adnan Muzaki, Kiki; Ahmad Fudhaili; Habil Abyad; Faisal Mahmoud Adam (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
This study examines the canonization process of Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Ibn Ḥibbān, considering that both possess similar critical authority and methodology yet hold differing reputations. Employing a qualitative method with a historical-comparative approach, the study draws upon classical sources on tarājim al-ruwwāt, historiography, and al-jarḥ wa al-ta‘dīl, as well as relevant contemporary academic scholarship. The findings demonstrate that al-Bukhārī’s methodological superiority provided a strong foundation for the widespread acceptance of his work. However, the canonical status of Ṣaḥīḥ al-Bukhārī did not emerge solely from methodological precision and personal authority, but also from layered social processes, including traditions of scholarly criticism and defense, networks of knowledge transmission, and political as well as institutional support. By contrast, Ṣaḥīḥ Ibn Ḥibbān who has comparable methodical and personal authority   did not undergo the same social and historical trajectory, so that it does have the same reputation as al-Bukhari. This study fills an analytical gap in ḥadīth studies by demonstrating that the divergent historical trajectories of these two collections were not rooted in methodological disparities only, but also in distinct socio-historical contexts, scholarly networks, and political patronage.